Acro-spondylo-pubic dysostosis associated with cataracts, microcephaly, and normal intelligence - Chacon-Camacho, Oscar F.; Villegas-Ruiz, Vanessa; Buentello-Volante, Beatriz; Piña-Aguilar, Raul E.; Peláez-González, Hugo; Ramírez, Magdalena; González-Rodríguez, Johanna; Zenteno, Juan Carlos (American journal of medical genetics. Part A, 2015)
We report on an adult male with normal intelligence who exhibited an unusual combination of microcephaly, dysostoses of limbs, vertebrae, patellae, and pubic bone, camptodactyly of all fingers, and syndactyly of toes, absent nails on thumbs and some fingers, bilateral cataract, cryptorchidism, polythelia, and nipple‐like skin pigmentations of shoulders and upper back. We have been unable to find a description of a similar combination of manifestations in literature. The cause of the anomalies remains unknown. © 2014 Wiley Periodicals, Inc.